Impact of dental pulp cells-derived small extracellular vesicles on the properties and behavior of dental pulp cells: an in-vitro study - Dina A. Hammouda; Alaa M. Mansour; Ahmed R. Zaher; Mohammed E. Grawish (BMC Oral Health)
Abstract Background Dental pulp cells-derived small extracellular vesicles (DPCs-sEVs) had shown immunomodulatory, anti-inflammatory, and tissue function restorative abilities. Therefore, DPCs-sEVs should be considered as a promising regenerative tool for dentin-pulp complex or whole pulp regeneration. This study aimed to evaluate the effect of DPCs-sEVs on the proliferation rate, migration capability, and expression pattern of DPCs for osteo/odontogenic gene markers in comparison with mineral trioxide aggregate (MTA). Methods DPCs-sEVs were isolated from rats’ incisors by ultracentrifugation technique. Immunophenotypic characterization, morphology, size, and protein concentration of DPCs-sEVs were monitored and analyzed using flow cytometry (FC), transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and bicinchoninic acid assay (BCA). In addition, the TSG101, CD63, and the cytosolic protein syntenin of sEVs markers were immunodetected using Western blotting. Cell cultures of DPCs from the third passage were left untreated and considered as a control (group I), whereas other cultured cells were treated with 50 µg/mL DPCs-sEVs (group II), 0.2 mg/mL MTA extract (group III), or their combination (50 µg/mL DPCs-sEVs + 0.2 mg/mL MTA extract (group IV). 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay, transwell migration assay, and real-time polymerase chain reaction were used for assessing proliferation, migration, and specific gene expression patterns. Results The DPCs-sEVs increased DPCs proliferation, and MTA enhanced their effects. The viability and proliferative capacity of DPCs treated with 50 µg/mL DPCs-sEVs + 0.2 mg/mL MTA-conditioned medium was significantly higher when compared with the other groups. The cell migration was more prominent in the group treated with 0.2 mg/mL MTA-conditioned medium than in the group treated with 50 µg/mL DPCs-sEVs. DPCs treated with 50 µg/mL DPCs-sEVs + 0.2 mg/mL MTA extract showed a significant increase in the migration ability of DPCs in comparison with other ones. Moreover, the combination group showed the greatest expression of dentin sialophosphoprotein (Dspp), osteocalcin (Ocn), collagen type I (Col1), and runt-related transcription factor 2 (Runx2). Conclusion MTA and sEVs together could be a powerful combination for regenerative endodontics. Clinical trial number Not applicable.